Low frequency approximation of mutual modal radiation efficiency of a vibrating rectangular plate - Zawieska, W.M.; Rdzanek, W.P. (Archives of Acoustics, 2006)
This paper presents some elementary formulations for the mutual modal radiation efficiencyof a simply supported rectangular plate embedded into a rigid infinite baffle. The magnitudemakes it possible to introduce the intermodal plate’s interactions into the total radiationefficiency of the plate vibrating under the influence of an external surface force. Theapproximate formula has been expressed as a combinations of some trigonometric and specialfunctions. The formula is convenient for some numerical computations of the modal and totalradiation efficiency values of the plate.